The Influence of Motivation and Work Discipline on the Performance of Civil Servants at the Department of Public Housing and Residential Areas of Padang City - Vika Fania Ayu Melani; Rahmadhona Fitri Helmi (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Improving the performance of the State Civil Apparatus (ASN) is essential for strengthening the effectiveness and accountability of government organizations, particularly through enhanced employee motivation and consistent work discipline. This study examined the partial and simultaneous effects of work motivation and work discipline on ASN performance at the Department of Public Housing and Residential Areas of Padang City. A quantitative approach with an associative research design was employed. The study involved all 57 ASN employees in the department, who were selected using saturated sampling. Data were collected through questionnaires and observations and analyzed using multiple linear regression. The findings demonstrated that work motivation and work discipline had positive and statistically significant effects on ASN performance, both individually and collectively. Employees with higher motivation and stronger work discipline tended to demonstrate better work quality, responsibility, and productivity. The study concludes that motivation and work discipline are important determinants of ASN performance within government institutions. These findings contribute empirical evidence to public human resource management and provide practical implications for government agencies seeking to improve employee performance through motivational strategies, consistent enforcement of work discipline, and systematic performance evaluation.